CONTENT AND CHARACTERISTICS OF TRAINING WITH YOUNG BOXERS (American Journal of Interdisciplinary Research and Development, 2022)
In this article, the work on the organization of training sessions with boxers aged 14-15 has been studied and scientifically analyzed and summarized.